Between historical-cultural psychology and sociology: School failure, school meanings and relations with knowledge (Revista Contexto & Educação, 2025)
This study examines the dynamics of schooling and its respective educational processes, based on the understanding that schools are shaped by specific socio-historical processes that have influenced and characterized this institution in its known contemporary form and culture. Within this scope, the thematic focus is the socio-historical production of school failure in relation to the meanings of schooling and students' relationships with knowledge. The justification for this research lies in the increasing questioning of the legitimacy and centrality of schools in educational processes since the late 1980s, reaching its peak with contemporary homeschooling movements. It is precisely in this context—where the traditional notion of school failure and the attempt to decentralize schooling in educational processes converge—that the following question arises: In a social context centered on material-economic individualization, how is schooling perceived and understood by segments of subordinated social classes as possible indicators for understanding school failure? Therefore, this study aims to understand how young people from marginalized social classes relate to school knowledge by analyzing different aspects of school failure in the construction of meanings associated with schooling. The research is based on bibliographic investigation, stemming from a theoretical-empirical master's study. The analytical approach is guided by the sociological theory of historical-dialectical materialism developed by Karl Marx and Friedrich Engels, in conjunction with the historical-cultural psychology of Lev Vygotsky and collaborators.
Keywords: School Success-Failure; Meanings of Schooling; Sign and Mediation